Formic acid and formate salts for chemical vapor deposition of copper on glass substrates at atmospheric pressure. (28th September 2021) - Mokhtari, Omid; Conti, Fosca; Saccon, Rodolfo; Bhogaraju, Sri Krishna; Elger, Gordon
Abstract : Deposition of copper on glass slides is obtained at atmospheric pressure using copper microparticles and formic acid or copper formate. Abstract : Chemical vapor deposition (CVD) typically occurs at pressures below 100 kPa because the quality of the produced film usually degrades at higher pressures. Two different approaches of CVD are presented in this study to successfully deposit thin films of copper on glass substrates at atmospheric pressure. The CVD processes occurred as a result of sublimation and thermal decomposition of Cu formate salts. The chemical composition and morphology of the deposited layers were investigated using X-ray diffraction, infrared spectroscopy, and scanning electron microscopy. The thickness of the layers was increased with a series of deposition cycles and was analysed using X-ray fluorescence spectroscopy and profilometry. The best results were obtained using Cu formate powder as the starting material and operating under a N2 atmosphere at 240 °C and 1 atm. A thickness of 600 nm was obtained after 10 deposition cycles. The resistivity values of Cu films were 2.6 × 10 −7 and 8 × 10 −8 Ω m after 5 and 10 cycles of deposition, respectively.